Implementation of parallel zero‐voltage switching converter with series‐connected transformers. (6th October 2011) - Lin, Bor‐Ren; Cheng, Chih‐Yuan
SUMMARY: This paper presents a parallel zero‐voltage switching (ZVS) DC–DC converter with series‐connected transformers. In order to increase output power, two transformers connected in series are used in the proposed converter. Two buck‐type converters connected in parallel have the same switching devices. The primary windings of series‐connected transformers can achieve the balanced secondary winding currents. The current doubler rectifiers with ripple current cancellation are connected in parallel at the output side to reduce the current stress of the secondary winding. Thus, the current ripple on the output capacitor is reduced, and the size of the output choke and output capacitor are reduced. Only two switches are used in the proposed circuit instead of four switches in the conventional parallel ZVS converter to achieve ZVS and output current sharing. Therefore, the proposed converter has less power switches. The ZVS turn‐on is implemented during the commutation stage of two complementary switches such that the switching losses and thermal stresses on the semiconductors are reduced. Experimental results for a 528‐W (48 V/11 A) prototype are presented to prove the theoretical analysis and circuit performance. Copyright © 2011 John Wiley & Sons, Ltd.